Neuroprotective effects of Vernonia amygdalina and Moringa oleifera in alloxan-induced diabetic Wistar rats - Chidimma, Acharaike Amarachi; Ofoego, Uzozie Chikere; Ezejindu, Damian Nnabuihe; Demshimeno, Paul Matthew; Obinwa, Makuachukwu Francisca; Obinwa, Benedict Nzube (Rzeszów University Press, 2025)
Introduction and aim. Diabetes mellitus is a metabolic disorder that affects multiple organs, including the hippocampus, a key region involved in memory. This study aimed to investigate the neuroprotective and antidiabetic effects of Vernonia amygdalina and Moringa oleifera in an alloxan-induced diabetic rat model. Materials and methods. Thirty-five adult Wistar rats were randomized into seven groups and treated with aqueous extracts of V. amygdalina, M. oleifera, their combination, or glibenclamide for 30 days following alloxan-induced diabetes. Fasting blood glucose (FBG), hippocampal acetylcholinesterase (AChE) activity, cognitive performance (Morris Water Maze test) and histopathological changes in the hippocampus were evaluated. Results. Alloxan significantly increased FBG (20.68±1.04 mmol/L), AChE activity (40.40±0.40 nmol/mL), and escape latency (51.75±4.39 sec), and reduced hippocampal cell density. Treatment with V. amygdalina and M. oleifera reduced FBG (8.29±0.93 mmol/L), AChE activity (34.50±0.30 nmol/mL), and escape latency (3.39±0.45 sec), and improved hippocampal histoarchitecture. Conclusion. V. amygdalina and M. oleifera demonstrated neuroprotective and antidiabetic effects in diabetic rats. These results support their potential as adjunct agents to prevent diabetes-induced cognitive dysfunction.
The protocol for the study was approved by the Ethics Committee, Faculty of Basic Medical Sciences, Nnamdi Azikiwe Universitty, Nnewi Campus and was assigned the reference number NAU/CHS/NC/FBMS/472.
Keywords: acetylcholinesterase; diabetes mellitus; hippocampus; Moringa oleifera; Vernonia amygdalina